Undertreatment of Mental Health Problems in Adults With Diagnosed Diabetes and Serious Psychological Distress: The Behavioral Risk Factor Surveillance System, 2007 - Li, Chaoyang (American Diabetes Association, 2010)
OBJECTIVE: To assess the prevalence and correlates of undertreatment for mental health problems among adults with diabetes and serious psychological distress (SPD). RESEARCH DESIGN AND METHODS: We analyzed data of adults aged ≥18 years from the 2007 Behavioral Risk Factor Surveillance System. SPD was assessed with the Kessler-6 scale. RESULTS: The prevalence of untreated SPD was estimated to be 2.1 ± 0.1% (mean ± SE), 3.4 ± 0.3%, and 2.0 ± 0.1% in the total population, diabetic population, and nondiabetic population, respectively. Among people with SPD, those with diagnosed diabetes had a lower rate of undertreatment for mental health problems (45.0%) than those without diabetes (54.9%) (P = 0.002). Nonwhite race/ethnicity, advanced age, lack of health insurance, and currently being employed were associated with increased likelihood of undertreatment for mental health problems (P < 0.05). CONCLUSIONS: People with diagnosed diabetes may be screened for SPD and treated for specific mental health problems in routine health care.